Pemanfaatan Bakteri Selulolitik dan Xilanolitik yang Potensial untuk Dekomposisi Jerami Padi - Nur, Hasrul Satria; Meryandini, Anja; Hamim, . (UNIVERSITY OF LAMPUNG, 2009)
There were 3 prospective isolates of cellulolytic bacteria resulted from the total of 31 isolates we found, i.e. C4-4, C5-1, and C11-1. Four combinations of bacteria including C4-4 + Xilanolytic (A), C5-1 + Xilanolytic (B), C11-1 + Xilanolytic (C), 45I-3 + 234P-16 (D), and control (E, without bacteria) were applied as inoculant of rice straw decomposition. In the incubation period the pH-H2O value of C4-4 + Xilanolytic (A) and C5-1 + Xilanolytic (B) was relatively stable. The C/N ratio of all treatments decreased after 3 weeks of incubation. The C/N ratio value of A, B, C, D and E treatments were 22.48, 23.43, 27.49, 26.82, and 29.53 respectively. Decomposition rate all of combination treatments were faster than the control. The content of macro-micro nutrient of A, B, C, and D treatments increased in the end of measurement, while the control didn’t. The physical characteristic of substrate after incubation was better in A and B treatments that others. The result indicated that the combination of C4-4 + Xilanolytic (A) and C5-1 + Xilanolytic (B) bacteria were the best combination for decomposition of rice straw.